Triangulation: An imperial power device - Dzenovska, Dace (HAU journal of ethnographic theory, 2024)
Drawing on Katherine Verdery’s Transylvanian villagers and fieldwork in Latvia, this article discusses triangulation as an imperial power device whereby one actor makes an alliance with another to influence a third. The social and political field within which triangulation is deployed is not a flat world of nation-states or networks, but a three-dimensional social and political field. The actors involved are not of the same kind (e.g., ethnic groups or nation-states), nor are they arranged in binary pairs (e.g., colonizer and the colonized). Most importantly, triangulation is not a power device deployed solely by the empire’s agents. It is also used by subjects of empire to pursue their own ends.